“Output Research Supporting Class” Manuscript Writing Training to Avoid Misconduct in an Islamic Perspective - Yuniarti, Lelly; Batara, Triando; Garna, Herry; Tejasari, Maya (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
The tridharma point that is most challenging for a lecturer to achieve is research, and currently, the benchmark for the research field is scientific publications. However, in reality, there are still many lecturers who are hampered in fulfilling research outputs in the form of scientific publications, this is because lecturers experience difficulties in compiling manuscripts of research results for publication. There are currently 144 lecturers at the Tasikmalaya Health Engineering Polytechnic and around 50% of the lecturers still have the functional position of expert assistant and do not have a functional position or teaching staff. This PKM aims to improve the ability of Tasikmalaya Health Polytechnic lecturers to compile manuscripts, avoid misconduct, and publish the manuscript in the intended journal. PKM methodThis is done using an Asset Based Community-Driven Development (ABCD) approach, namely focusing on the assets, potential and strengths of the Health Polytechnic lecturers. Workshop and coaching clinic preparing manuscripts, using reference management, and submitting manuscripts to journals. The research results showed that of the 50 participants who took part in the workshop, 15 lecturers succeeded in compiling manuscripts of research results, avoiding misconduct, and improving the manuscripts according to reviewer input. This shows the need for ongoing training and stimulation activities for lecturers in compiling research output.